Penentuan Kadar Fenolik, Tanin, Flavonoid, dan Saponin Ekstrak Etanol Daun Kenikir (Cosmos caudatus Kunth.) - Abidin, Zainal; Aminah, Aminah; Razak, Rais; Eka Putri, Andi Yuyun; M, Murti Nurhidayah; A, Aridha (PHARMACY UMI JOURNAL SYSTEM, 2024)
The kenikir plant is a tropical plant originating from Latin America that can easily grow in various places. The use of kenikir leaves (Cosmos caudatus Kunth.) as a medicinal plant has been widely used. People usually use kenikir leaves as traditional medicine. Kenikir leaves are extracted by maceration method using 96% ethanol solvent after which a liquid extract is obtained and then evaporated using a rotavapor so that a thick extract is obtained. This study aims to analyze the levels of phenolic compounds, tannins, flavonoids, and saponins contained in kenikir leaves (Cosmos caudatus Kunth.). Determination of levels using UV-Vis spectrophotometric method. The ethanol extract of kenikir leaves (Cosmos caudatus Kunth.) contains phenolic compounds, tannins, flavonoids, and saponins with the levels of each phenolic compound, tannins, flavonoids, and saponins respectively as follows: 43.592 mgGAE/g, 40.639 mgEAT/g, 36.319, and 142.527 mgSE/g.